Systematic literature survey: applications of LoRa communication - Lone Godfrey Future Kolobe; Caspar K. Lebekwe; Boyce Sigweni (Institute of Advanced Engineering and Science, 2020)
LoRa is a communication scheme that is part of the low power wide are network (LPWAN) technology using ISM bands. It has seen extensive documentation and use in research and industry due to its long coverage ranges of up-to 20Km or more with less than 14dB transmit power. Moreover, some applications report theoretical battery lives of upto 10years for field deployed modules utilising the scheme in WSN applications. Additionally, the scheme is very resilient to losses from noise, as well bursts of interference through its FEC. Our objective is to systematically review the empirical evidence of the use-cases of LoRa in rural landscapes, metrics and the relevant validation schemes. In addition the research is evaluated based on (i) mathematical function of the scheme (bandwidth use, spreading factor, symbol rate, chip rate and nominal bit rate) (ii) use-cases (iii) test-beds, metrics of evaluation and (iv) validation methods. A systematic literature review of published, refereed primary studies on LoRa applications was conducted. Using articles from 2010-2019. We identified 21 relevant primary studies. These reported a range of different assessments of LoRa. 10 out of 21 reported on novel use cases. As an actionable conclusion, the authors conclude that more work is needed in terms of field testing, as no articles could be found on performance/deployment in Botswana or South Africa despite the existence of LoRa networks in both countries. Thus researchers in the region can research propagation models performance, energy efficiency of the scheme and MAC layer as well as the channel access challenges for the region.